Positive electrode active material for lithium secondary battery and method for producing said positive electrode active material

By controlling the crystal grain size and primary particle diameter of lithium transition metal oxide in lithium secondary batteries, the active material achieves improved high-temperature performance and storage characteristics, addressing the thermal stability issues in existing technologies.

JP7655618B2Active Publication Date: 2025-04-02LG ENERGY SOLUTION LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022528132
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-05
Filing Date
2020-12-04
Publication Date
2025-04-02
Estimated Expiration
2040-12-04

AI Technical Summary

Technical Problem

Lithium transition metal oxides used in lithium secondary batteries suffer from poor thermal stability, leading to inferior high-temperature lifetime and storage properties.

Method used

A positive electrode active material is developed with lithium transition metal oxide particles having a crystal grain size of 160 nm or less and an average particle diameter of 0.6 μm or more, achieved through a method involving the preparation of a transition metal hydroxide precursor, mixing with lithium and boron-containing raw materials, and calcination at 760° C to 840° C.

Benefits of technology

The resulting positive electrode active material exhibits improved high-temperature lifetime, storage properties, and reduced gas generation, enhancing the overall performance of lithium secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655618000001
    Figure 0007655618000001
  • Figure 0007655618000002
    Figure 0007655618000002
  • Figure 0007655618000003
    Figure 0007655618000003
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material having a form of secondary particles formed by aggregation of primary particles, which includes a lithium transition metal oxide represented by Chemical Formula 1, in which the crystalline size of the lithium transition metal oxide is 160 nm or less and the average particle size of the primary particles is 0.6 μm or more, and a method for manufacturing the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2019-0160667, filed December 5, 2019, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.

[0002] The present invention relates to a positive electrode active material for a lithium secondary battery, a method for producing the positive electrode active material, and a positive electrode and a lithium secondary battery each including the positive electrode active material. [Background technology]

[0003] With the technological development and increasing demand for mobile devices, the demand for secondary batteries as an energy source is rapidly increasing. Among these secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.

[0004] Lithium transition metal composite oxides are used as the positive electrode active material of lithium secondary batteries, and among them, lithium cobalt composite metal oxides such as LiCoO2, which have high working voltage and excellent capacity characteristics, are mainly used. However, LiCoO2 has very poor thermal characteristics due to the instability of the crystal structure caused by delithiation. In addition, the LiCoO2 is expensive, so there is a limit to its mass use as a power source in fields such as electric vehicles.

[0005] As a material to be used in place of LiCoO2, lithium manganese composite metal oxides (LiMnO2 or LiMn2O4, etc.), lithium iron phosphate compounds (LiFePO4, etc.), lithium nickel composite metal oxides (LiNiO2, etc.), etc. have been developed. Among them, research and development on lithium nickel composite metal oxides, which have a high reversible capacity of about 200 mAh / g and therefore facilitate the realization of large-capacity batteries, has been actively carried out. However, LiNiO2 has inferior thermal stability compared to LiCoO2, and when an internal short circuit occurs due to external pressure in a charged state, the positive electrode active material itself decomposes, causing the battery to explode and catch fire. Therefore, as a method for maintaining the excellent reversible capacity of LiNiO2 and improving its low thermal stability, lithium transition metal oxides in which part of Ni is replaced with Co, Mn, or Al have been developed.

[0006] However, as described above, the lithium transition metal oxides substituted with Co, Mn or Al still have poor thermal stability, and therefore have problems in that when applied to batteries, they have poor high-temperature life characteristics and storage characteristics.

[0007] Therefore, there is a need for development of a positive electrode active material that can improve thermal stability and thereby improve life and storage characteristics at high temperatures. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Korean Patent No. 10-2004457 Summary of the Invention [Problem to be solved by the invention]

[0009] In order to solve the above problems, a first technical objective of the present invention is to provide a positive electrode active material in which the size of primary particles and the size of crystals are controlled, and which can improve high-temperature life characteristics and high-temperature storage characteristics.

[0010] A second technical object of the present invention is to provide a method for producing the positive electrode active material.

[0011] A third technical object of the present invention is to provide a positive electrode containing the positive electrode active material.

[0012] A fourth technical object of the present invention is to provide a lithium secondary battery including the positive electrode. [Means for solving the problem]

[0013] The present invention provides a positive electrode active material having a form of secondary particles formed by aggregation of primary particles, the positive electrode active material comprising a lithium transition metal oxide represented by the following Chemical Formula 1, the crystalline size of the lithium transition metal oxide being 160 nm or less, and the average particle size of the primary particles being 0.6 μm or more. [Chemical formula 1] Li 1+a Ni x Co y M 1 z B w O2 In the above Chemical Formula 1, M 1 contains at least one of Mn and Al, and 0≦a≦0.5, 0.5≦x<1.0, 0 <y≦0.4、0<z≦0.4、0<w≦0.1である。

[0014] The present invention also provides a method for producing a positive electrode active material, the method including the steps of preparing a transition metal hydroxide precursor, and mixing the transition metal hydroxide precursor, a lithium source material, and a boron (B)-containing source material, followed by firing at 760°C to 840°C to produce a boron (B)-doped lithium transition metal oxide, the boron (B)-doped lithium transition metal oxide being represented by Chemical Formula 1 above, having a crystal grain size of 160 nm or less, and an average primary particle size of 0.6 μm or more.

[0015] The present invention also provides a positive electrode for a lithium secondary battery, comprising the positive electrode active material.

[0016] The present invention also provides a lithium secondary battery including the positive electrode for a lithium secondary battery. Effect of the Invention

[0017] In the manufacturing method of the present invention, boron is doped during the production of lithium transition metal oxide and then sintered at a specific temperature, so that the crystal size of the lithium transition metal oxide is small and the primary particles are large.

[0018] As described above, the positive electrode active material containing the lithium transition metal oxide of the present invention, in which the crystal size and primary particle size are controlled, exhibits excellent high-temperature life characteristics, high-temperature storage characteristics, and gas generation characteristics when applied to a secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present invention will now be described in more detail.

[0020] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0021] In the present invention, the term "crystalline" refers to a single crystal particle unit having a regular atomic arrangement. The size of the crystalline can be measured by analyzing XRD data obtained by X-ray diffraction analysis of the positive electrode active material powder using a Rietveld refinement method. In this case, the X-ray diffraction analysis was performed using a Bruker D8 Endeavor (light source: Cu-Kα, λ=1.54Å) equipped with a LynxEye XE-T position sensitive detector. The sample was placed in the groove of a general powder holder, the surface of the sample was made uniform using a slide glass, and the height of the sample was filled to match the edge of the holder, and then the measurement was performed under the conditions of FDS 0.5°, step size = 0.02° in the region of 2θ = 15° to 90°, and total scan time = about 20 minutes.

[0022] The measured data were subjected to Rietveld refinement, taking into account the charge at each site (metals at transition metal sites are +3, Ni at Li sites is +2) and cation mixing. Specifically, when analyzing the grain size, instrumental broadening was taken into account using the Fundamental Parameter Approach (FPA) built into the Bruker TOPAS program, and the entire peak of the measurement range was used during fitting. Peak shape was fitted using only the Lorenzian contribution as the First Principle (FP) of the peak types available in TOPAS, and strain was not considered.

[0023] In the present invention, the term "primary particle" refers to the smallest particle unit that can be distinguished as one mass when observing a cross section of a positive electrode active material through a scanning electron microscope (SEM), and can consist of one crystal grain or multiple crystal grains. In the present invention, the average particle size of the primary particles is measured by measuring the particle size of each particle distinguished in a cross-sectional SEM image of the positive electrode active material particle and then calculating the arithmetic average value of these.

[0024] In the present invention, the term "secondary particles" refers to a secondary structure formed by the aggregation of a plurality of primary particles. The average particle size of the secondary particles can be measured using a particle size analyzer, and in the present invention, a Microtrac S3500 was used as the particle size analyzer.

[0025] In the present invention, the "particle size Dn" of the positive electrode active material means the particle size at the n% point of the volume cumulative distribution of particle size. 50 is the particle size at the 50% point of the cumulative volume distribution by particle size, and D 90 is the particle size at the 90% point of the cumulative volume distribution by particle size, and D 10 is the particle size at 10% of the cumulative volume distribution by particle size. The above Dn can be measured using the laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and the particle size distribution is calculated by measuring the difference in the diffraction pattern due to the particle size when the particles pass through a laser beam. D is determined by calculating the particle diameter at the 10%, 50%, and 90% points of the cumulative volume distribution by particle size in the measuring device. 10 , D 50 and D. 90 can be measured.

[0026] positive electrode active material The inventors have discovered that by controlling the size of the primary particles and the size of the crystal grains of a lithium transition metal oxide within specific ranges, it is possible to improve the high-temperature life characteristics, high-temperature storage characteristics, and gas generation characteristics of a positive electrode active material, and have thus completed the present invention.

[0027] The positive electrode active material according to the present invention includes a lithium transition metal oxide having a form of secondary particles formed by aggregation of primary particles, wherein the size of crystal grains is 160 nm or less and the average particle diameter of the primary particles is 0.6 μm or more.

[0028] At this time, the lithium transition metal oxide can be a lithium transition metal oxide in which the molar ratio of nickel to the total molar number of transition metals is 50 mol% or more, preferably 60 mol% or more, and which is doped with boron (B).

[0029] Preferably, the lithium transition metal oxide can be represented by the following Chemical Formula 1.

[0030] [Chemical Formula 1] Li 1+a Ni x Co y M 1 z B w O2

[0031] In Chemical Formula 1 above, M 1 is one or more of Mn or Al, and preferably can be Mn or a combination of Mn and Al.

[0032] The 1 + a represents the molar ratio of lithium in the lithium transition metal oxide, and 0 ≦ a ≦ 0.5, preferably 0 ≦ a ≦ 0.2, more preferably 0 ≦ a ≦ 0.1.

[0033] The x represents the molar ratio of nickel to the total transition metal elements in the lithium transition metal oxide, and 0.5 ≦ x < 1.0, preferably 0.6 ≦ x ≦ 0.98, more preferably 0.6 ≦ x ≦ 0.95.

[0034] The y represents the molar ratio of cobalt to the total transition metal elements in the lithium transition metal oxide, and 0 < y ≦ 0.4, preferably 0 < y ≦ 0.3, more preferably 0.05 ≦ y ≦ 0.3.

[0035] wherein z represents the molar ratio of the M element to the total transition metal elements in the lithium transition metal oxide, and 0 < z ≤ 0.4, preferably 0 < z ≤ 0.3, more preferably 0.01 ≤ z ≤ 0.3. 1 wherein w represents the molar ratio of boron in the lithium transition metal oxide, and 0 < w ≤ 0.1, preferably 0 < w ≤ 0.05, more preferably 0 < w ≤ 0.02.

[0036]

[0037] The lithium transition metal oxide according to the present invention can be produced by mixing a cathode active material precursor, a lithium raw material, and a boron-containing raw material, and then firing. When adding a boron-containing raw material during firing, boron (B) can lower the reaction temperature between the cathode active material precursor and the lithium raw material and perform firing at a relatively low temperature. The low firing temperature can suppress grain growth and obtain a lithium transition metal oxide with small grain size. Also, as described above, when boron (B) is present during firing, boron serves as a catalyst to promote the reaction between the cathode active material precursor and the lithium raw material, promoting the growth of primary particles, and a lithium transition metal oxide with larger primary particle size than the cathode active material produced without adding boron under the same firing conditions can be obtained.

[0038] Specifically, in the present invention, the average particle size of the primary particles of the lithium transition metal oxide can be 0.6 μm or more, preferably 0.6 μm to 1.3 μm, more preferably 0.6 μm to 1.0 μm. When the average particle size of the primary particles satisfies the above range, cracking of the particles can be suppressed during cathode manufacturing or the charge and discharge process of the battery, effectively suppressing deterioration of high-temperature storage characteristics and generation of a large amount of gas caused by fine powder in the cathode.

[0039] ​In addition, in the present invention, the lithium transition metal oxide may have a crystal grain size of 160 nm or less, preferably 100 nm to 160 nm. When the crystal grain size of the lithium transition metal oxide satisfies the above range, the generation of cracks in the positive electrode active material occurring during charging and discharging is minimized, the capacity retention rate with the progress of cycles is increased, and the resistance increase rate is suppressed, thereby improving high-temperature life characteristics.

[0040] The lithium transition metal oxide may have the form of secondary particles formed by agglomeration of primary particles.

[0041] When the positive electrode active material contains a lithium transition metal oxide in the form of secondary particles as described above, the contact surface between the positive electrode active material and the electrolyte is increased and the distance between lithium ions in the positive electrode active material is reduced, thereby achieving high capacity and high output characteristics.

[0042] In addition, the positive electrode active material may contain 0.02 to 0.3 parts by weight, preferably 0.05 to 0.2 parts by weight, of boron (B) based on 100 parts by weight of the lithium transition metal oxide represented by Chemical Formula 1. When the boron (B) is contained within the above range, the average particle size of the primary particles of the lithium transition metal oxide can be controlled within a desired range without decreasing the energy density. When the content of the doped boron (B) is less than the above range, the growth of the primary particles is small, so that fine powder is easily generated due to cracking of the particles during the manufacture of the positive electrode or the charging and discharging of the battery, and therefore, when applied to a battery, the high-temperature storage characteristics are deteriorated and a large amount of gas is generated, which may cause a swelling phenomenon. On the other hand, when the content of the boron (B) exceeds the above range, the energy density of the positive electrode active material may be reduced due to the addition of an excessive amount of the doping element.

[0043] On the other hand, in the present invention, the positive electrode active material has an average secondary particle diameter D 50 In other words, the positive electrode active material according to the present invention can include two types of lithium transition metal oxides having different average particle diameters D 50The average particle size of the secondary particles of the large-particle lithium transition metal oxide is D 50 The large particle size lithium transition metal oxide and the small particle size lithium transition metal oxide may each independently have a composition represented by Chemical Formula 1, and the compositions of the large particle size lithium transition metal oxide and the small particle size lithium transition metal oxide may be the same or different, but it is more preferable that the compositions of the large particle size lithium transition metal oxide and the small particle size lithium transition metal oxide are the same.

[0044] On the other hand, the average particle size (D 50 ) can be 7 μm to 20 μm, preferably 8 μm to 18 μm, and more preferably 8 μm to 16 μm, and the average particle size (D 50 ) can be 1 μm to 7 μm, preferably 3 μm to 7 μm, and more preferably 3 μm to 6 μm. When using a positive electrode active material having a bimodal particle size distribution as described above, a positive electrode having high electrode density and energy density can be formed.

[0045] Method for producing positive electrode active material Next, a method for producing the positive electrode active material according to the present invention will be described.

[0046] The method for producing a positive electrode active material according to the present invention includes the steps of (1) preparing a transition metal hydroxide precursor, and (2) mixing the transition metal hydroxide precursor, a lithium source material, and a boron (B)-containing source material, and calcining the mixture at 760°C to 840°C to produce a boron (B)-doped lithium transition metal oxide.

[0047] In this case, the boron (B)-doped lithium transition metal oxide is represented by the formula 1, and has a crystal grain size of 160 nm or less and an average primary particle size of 0.6 μm or more. The lithium transition metal oxide is as described above, and therefore a detailed description thereof will be omitted.

[0048] Hereinafter, the method for manufacturing a positive electrode active material according to the present invention will be described in more detail.

[0049] First, a transition metal hydroxide precursor is prepared (first step).

[0050] At this time, the transition metal hydroxide precursor can be a transition metal hydroxide containing nickel, cobalt, and metal element M 1 (At this time, M 1 includes at least one of Mn or Al), and preferably, the molar ratio of nickel to the total molar number of transition metals in the transition metal hydroxide can be 50 mol% or more, preferably 60 mol% or more.

[0051] The transition metal hydroxide precursor can be purchased and used as a commercially available precursor for a positive electrode active material, or can be manufactured by a method for manufacturing a precursor for a positive electrode active material well-known in the art.

[0052] Preferably, the transition metal hydroxide precursor can be represented by the following Chemical Formula 2.

[0053] [Chemical Formula 2] Ni x1 Co y1 M 1 z1 (OH)2

[0054] In Chemical Formula 2, M 1 can include at least one of Mn or Al.

[0055] On the other hand, x1 can be 0.5 ≦ x1 < 1.0, preferably 0.6 ≦ x1 ≦ 0.98, more preferably 0.6 ≦ x1 ≦ 0.95.

[0056] y1 can be 0 < y1 ≦ 0.4, preferably 0 < y1 ≦ 0.3, more preferably 0.05 ≦ y1 ≦ 0.3.

[0057] The z1 can be 0 < z1 ≤ 0.4, preferably 0 < z1 ≤ 0.3, more preferably 0.01 ≤ z1 ≤ 0.3.

[0058] At this time, x1 + y1 + z1 = 1 can be satisfied.

[0059] Next, the transition metal hydroxide precursor, the lithium raw material substance, and the boron (B)-containing raw material substance are mixed and fired at 760 °C to 840 °C to produce a boron (B)-doped lithium transition metal oxide (second step).

[0060] As the boron (B)-containing raw material substance, sulfates, nitrates, acetates, halides, hydroxides, oxyhydroxides, etc. containing boron (B) can be used, and as long as it can be dissolved in a solvent such as water, it can be used without particular limitation. Specifically, the boron-containing raw material substance can be H3BO3, B2O3, B4C, BF3, (C3H7O)3B, (C6H5O)3B, [CH3(CH2)3O]3B, C 13 H 19 O3, C6H5B(OH)2, B2F4, or a combination thereof, but is not limited thereto.

[0061] Also, as long as the lithium raw material substance is a compound containing a lithium source, it can be used without particular limitation, and preferably, at least one selected from the group consisting of lithium carbonate (Li2CO3), lithium hydroxide (LiOH·H2O), LiNO3, CH3COOLi, and Li2(COO)2 can be used.

[0062] On the other hand, the transition metal hydroxide precursor and the boron (B)-containing raw material substance can be mixed in an amount such that the total molar number of the transition metal: the molar number of boron is 0.97:0.03 to 0.998:0.002, preferably 0.975:0.025 to 0.995:0.005.

[0063] In addition, the lithium source material may be mixed in an amount such that the ratio of the number of moles of lithium to the total number of moles of transition metal and boron, i.e., (number of moles of Li / (number of moles of transition metal+number of moles of boron)) is 1.0 to 1.2, preferably 1.0 to 1.1, and more preferably 1.01 to 1.08.

[0064] When the compounding ratio of the transition metal hydroxide, the boron-containing raw material and the lithium raw material satisfies the above range, the size of the primary particles and the size of the crystal grains can be controlled within the desired range.

[0065] The mixture of the transition metal precursor, lithium source material and boron-containing source material is then calcined.

[0066] In this case, the firing temperature can be 760°C to 840°C, and preferably 760°C to 800°C.

[0067] When the calcination process is performed in the above-mentioned temperature range, the crystal growth is suppressed by the relatively low calcination temperature, and a positive electrode active material having a crystal grain size of 160 nm or less, preferably 100 nm to 160 nm, can be synthesized. Furthermore, the inside of the particles of the positive electrode active material grows densely due to the low calcination temperature, so that the strength of the particles is improved and cracking of the particles of the positive electrode active material during the manufacture of the electrode or during charging and discharging of the battery can be suppressed.

[0068] On the other hand, when the firing process is performed at a temperature exceeding 840° C., the crystal grain size of the positive active material may be larger than the range of the present invention due to over-firing, which causes the particles to grow unevenly. In this case, the volume change in the unit lattice that occurs during charging and discharging is large compared to a positive active material that satisfies the crystal grain size of the present invention, and therefore, cracks are more likely to occur in the positive active material as the cycle progresses, which may reduce the high-temperature life characteristics.

[0069] Meanwhile, the calcination may be carried out for 15 to 30 hours, preferably 17 to 25 hours. When the calcination time is within the above range, a lithium transition metal oxide having a desired average particle size of primary particles and crystal grain size can be produced. If the calcination time is too short, the primary particles cannot grow sufficiently, and if the calcination time is too long, the crystal grains may grow excessively large.

[0070] According to the production method of the present invention, even if the firing temperature is lowered during the production of a positive electrode active material due to the boron (B) contained in the boron (B)-containing raw material, the growth of the primary particles of the positive electrode active material is promoted by the boron (B), so that a lithium transition metal oxide having an average particle size of the primary particles of 0.6 μm or more can be produced even when firing is performed at a relatively low firing temperature.

[0071] In general, when a high Ni-containing transition metal hydroxide precursor, in which the Ni content is 50 mol% or more relative to the total moles of transition metals, is mixed with a lithium source material (e.g., LiOH·H2O) and fired, the reaction with the transition metal hydroxide precursor begins when the lithium melts, and since the melting point of LiOH·H2O is about 400°C, the transition metal hydroxide precursor reacts with lithium at temperatures above 400°C. However, since B can react with Li at about 150°C, B and Li react at 150°C, and B can also act as a catalyst when Li reacts with the transition metal hydroxide precursor at temperatures above 450°C. As a result, when the reaction temperature of Li and the transition metal hydroxide precursor is lowered and B is applied, even if the calcination is performed at a temperature lower than the calcination temperature of a conventional mixture of a transition metal hydroxide precursor containing a high nickel content and a lithium raw material, the growth of the primary particles of the positive electrode active material is promoted by B, and a lithium transition metal oxide having a relatively large average particle size of the primary particles can be obtained.

[0072] Therefore, according to the manufacturing method of the present invention, in which a boron-containing raw material is added during firing and firing is performed at a specific temperature, it is possible to produce a lithium transition metal oxide having an average primary particle size of 0.6 μm or more and a crystal size of 160 nm or less.

[0073] positive electrode The present invention also provides a positive electrode for a lithium secondary battery, which contains the above-mentioned positive electrode active material.

[0074] Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector and including the above-mentioned positive electrode active material.

[0075] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can usually have a thickness of 3 to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive force of the positive electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0076] The positive electrode active material layer may contain a conductive material and a binder in addition to the positive electrode active material.

[0077] In this case, the positive electrode active material may be included in an amount of 80 to 99 wt %, more specifically, 85 to 98 wt %, based on the total weight of the positive electrode active material layer. When included in the above content range, excellent capacity characteristics can be exhibited.

[0078] In this case, the conductive material is used to give conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these can be used alone or in combination. The conductive material can be contained in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.

[0079] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.

[0080] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by coating a positive electrode mixture prepared by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent on the entire positive electrode assembly, followed by drying and rolling. In this case, the types and contents of the positive electrode active material, binder, and conductive material are as described above.

[0081] The solvent may be a solvent commonly used in the art, and may include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to have a viscosity that can provide excellent thickness uniformity during subsequent application for the manufacture of a positive electrode, taking into consideration the coating thickness of the positive electrode composite and the manufacturing yield.

[0082] Alternatively, the positive electrode can be produced by casting the positive electrode mixture on a separate support, peeling it off from the support, and laminating the resulting film on a positive electrode current collector.

[0083] Lithium secondary battery In addition, the present invention can provide an electrochemical device including the positive electrode. The electrochemical device can be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0084] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Since the positive electrode is as described above, a detailed description thereof will be omitted, and only the remaining components will be described in detail below.

[0085] Also, the lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0086] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0087] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0088] The negative electrode active material layer includes a negative electrode active material, and optionally a binder and a conductive material.

[0089] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites, and any one or a mixture of two or more of these may be used. Also, a thin film of metallic lithium may be used as the negative electrode active material. Also, the carbon material may be either low crystalline carbon or high crystalline carbon. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural graphite or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0090] The negative electrode active material may be included in an amount of 80% by weight to 99% by weight based on the total weight of the negative electrode active material layer.

[0091] The binder is a component that facilitates bonding between the conductive material, the active material, and the current collector, and is usually added in an amount of 0.1% by weight to 10% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0092] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of such conductive materials include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0093] For example, the negative electrode active material layer can be produced by applying a negative electrode mixture, which is prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent, onto a negative electrode current collector and drying the applied material; alternatively, the negative electrode mixture can be cast onto another support, and then peeled off from the support to obtain a film, which can be laminated onto the negative electrode current collector.

[0094] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery can be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent humidification ability of the electrolyte is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, etc. can be used. In addition, a coated separator containing a ceramic component or a polymeric material can be used to ensure heat resistance or mechanical strength, and can be selectively used in a single layer or multilayer structure.

[0095] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0096] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0097] The organic solvent may be any solvent capable of acting as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that can be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and mixtures of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can enhance the charge / discharge performance of the battery and low viscosity linear carbonate-based compounds (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc.) are more preferred.

[0098] The lithium salt can be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably within the range of 0.1 to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively.

[0099] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in the capacity of the battery, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 parts by weight based on 100 parts by weight of the total weight of the electrolyte.

[0100] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in portable devices such as mobile phones, notebook computers and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0101] According to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.

[0102] The battery module or battery pack may be used as a power source for one or more medium- to large-sized devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0103] The external shape of the lithium secondary battery of the present invention is not particularly limited, but may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.

[0104] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery in a medium- to large-sized battery module including a large number of battery cells.

[0105] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the examples according to the present invention can be modified into various other forms, and the scope of the present invention should not be interpreted as being limited to the examples described below. The examples of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.

[0106] Example 1 Ni 0.6 Co 0.2 Mn 0.2 The precursor represented by (OH)2, LiOH·H2O and H3BO3 were mixed so that the molar ratio of transition metals (Me):Li:B was 0.97:1.02:0.03, and the mixture was heat-treated at 780 °C for 23 hours to produce a B-doped positive electrode active material.

[0107] Example 2 A positive electrode active material was prepared in the same manner as in Example 1, except that the heat treatment was performed at 790°C.

[0108] Comparative Example 1 A positive electrode active material was prepared in the same manner as in Example 1, except that the heat treatment was performed at 750°C.

[0109] Comparative Example 2 A positive electrode active material was produced in the same manner as in Example 1, except that the heat treatment was performed at 850°C.

[0110] Comparative Example 3 Ni 0.6 Co 0.2 Mn 0.2 The precursor represented by (OH)2 and LiOH·H2O were mixed so that the molar ratio of transition metal (Me):Li was 1:1.02, and the mixture was heat-treated at 740°C for 23 hours to produce the positive electrode active material.

[0111] Comparative Example 4 Ni 0.6 Co 0.2 Mn 0.2 The precursor represented by (OH)2 and LiOH·H2O were mixed so that the molar ratio of transition metal (Me):Li was 1:1.02, and the mixture was heat-treated at 850°C for 23 hours to produce the positive electrode active material.

[0112] Comparative Example 5 Ni 0.6 Co 0.2 Mn 0.2 The precursor represented by (OH)2, LiOH·H2O and H3BO3 were mixed so that the molar ratio of transition metals (Me):Li:B was 0.92:1.02:0.08, and the mixture was heat-treated at 780 °C for 23 hours to produce a B-doped positive electrode active material.

[0113] Experimental Example 1: Confirmation of the characteristics of positive electrode active material particles (1) Average particle size of the primary particles of the positive electrode active material The average particle size of the primary particles of the positive electrode active materials produced in Examples 1 and 2 and Comparative Examples 1 to 5 was measured.

[0114] Specifically, a scanning electron microscope was used to observe cross-sectional images of the positive electrode active materials produced in Examples 1-2 and Comparative Examples 1-5, and the sizes of 100 primary particles in the cross-sections of the positive electrode active materials were measured, and the arithmetic mean value of these was then measured as the average particle size of the primary particles. The measurement results are shown in Table 1 below.

[0115] (2) Positive electrode active material crystal grain size The crystal grain sizes of the primary particles of the positive electrode active materials produced in Examples 1 and 2 and Comparative Examples 1 and 2 were measured.

[0116] Specifically, X-ray diffraction analysis was performed using a Bruker D8 Endeavor (Cu-Kα, λ=1.54Å) equipped with a LynxEye XE-T position sensitive detector, and the obtained XRD data was analyzed to measure the grain size. The X-ray diffraction analysis conditions and data processing method were as described above. The measurement results are shown in Table 1 below.

[0117] [Table 1]

[0118] From Table 1, it can be seen that in the case of the positive electrode active material manufactured according to Examples 1 and 2 in which boron doping was performed and sintering was performed at 760 to 840 ° C., the average particle size of the primary particles was 0.6 μm or more, and the size of the crystal grains was 160 nm or less. On the other hand, in the case of Comparative Examples 1 and 2 in which boron doping was performed but the sintering temperature was out of the range of the present invention, it was found that the average particle size and the size of the crystal grains of the primary particles did not meet the range of the present invention. In addition, in the case of Comparative Example 3 in which boron doping was not performed and sintering was performed at a low temperature, it was confirmed that both the average particle size and the size of the crystal grains of the positive electrode active material were low and below the range of the present invention. In the case of Comparative Example 4 in which boron doping was not performed and heat treatment was performed at a high temperature, it can be confirmed that the size of the crystal grains of the positive electrode active material was formed larger than those of Examples 1 and 2, while the size of the primary particles was formed smaller.

[0119] Meanwhile, in the case of Comparative Example 5, it was confirmed that the reactivity between the precursor and the lithium source material was reduced due to the inclusion of an excessive amount of boron, leading to over-firing, and the sizes of both the primary particles and the crystals were beyond the range of the present invention.

[0120] Experimental example 2: High temperature life characteristics Secondary batteries were manufactured using the positive electrode active materials manufactured in Examples 1 and 2 and Comparative Examples 1 to 5, and the high-temperature characteristics of each of the secondary batteries including the positive electrode active materials of Examples 1 and 2 and Comparative Examples 1 to 5 were evaluated.

[0121] First, the positive electrode active materials, conductive materials, and binders prepared in Examples 1-2 and Comparative Examples 1-5 were mixed in a weight ratio of 92:3:4 in N-methylpyrrolidone (NMP) solvent to prepare a positive electrode slurry. The positive electrode slurry was applied onto an aluminum foil having a thickness of 20 μm, dried at 130° C., and then rolled to prepare a positive electrode.

[0122] Meanwhile, the negative active material, conductive material, and binder were mixed in a weight ratio of 96:1.1:2.9, and the mixture was added to distilled water as a solvent to prepare a negative active material slurry, which was then coated on a copper foil having a thickness of 10 μm, dried, and then roll-pressed to prepare a negative electrode.

[0123] A separator was interposed between the positive and negative electrodes to prepare an electrode assembly, which was then placed inside a battery case, and an electrolyte was injected into the case to prepare a lithium secondary battery. At this time, the electrolyte was prepared by dissolving 1M LiPF6 in an organic solvent in which ethylene carbonate (EC): dimethyl carbonate (DMC): diethyl carbonate (DEC) were mixed in a ratio of 1:2:1, and vinylene carbonate (VC) was injected at 2 wt% per 100 parts by weight of the total weight of the electrolyte, thereby preparing the lithium secondary batteries according to Examples 1-2 and Comparative Examples 1-5.

[0124] The lithium secondary batteries containing the positive electrode active materials of Examples 1 and 2 and Comparative Examples 1 to 5 were charged at 45° C. at a constant current of 0.5 C up to 4.2 V with a 0.05 C cutoff, and then discharged at a constant current of 0.5 C down to 3.0 V.

[0125] The above-mentioned charging and discharging behavior was counted as one cycle, and after repeating such a cycle 400 times, the capacity retention rates at 45° C. of the lithium secondary batteries of Examples 1 and 2 and Comparative Examples 1 to 5 were calculated, and the results are shown in Table 2 below.

[0126] [Table 2]

[0127] As shown in Table 2, it was confirmed that the secondary batteries using the positive electrode active materials prepared in Examples 1 and 2 had improved capacity retention rates due to high temperature cycles compared to the secondary batteries of Comparative Examples 1 to 5.

[0128] Experimental Example 3: High-temperature storage characteristics The high-temperature storage characteristics of the secondary batteries of Examples 1 and 2 and Comparative Examples 1 to 5 produced according to Experimental Example 2 were measured.

[0129] Specifically, the secondary batteries of Examples 1 and 2 and Comparative Examples 1 to 5 were each fully charged to 4.2 V, and then stored at 60° C. for 4 weeks.

[0130] Before storage, the discharge capacity and volume of the fully charged secondary battery were measured.

[0131] After 4 weeks, the stored secondary battery was charged to 4.2 V at a constant current of 0.5 C, and discharged to 3.0 V at a constant current of 0.5 C, and then the discharge capacity and volume were measured and compared with the discharge capacity and volume of the secondary battery measured before storage to calculate the capacity retention rate and volume change rate. The results are shown in Table 3 below.

[0132] [Table 3]

[0133] As shown in Table 3, it was confirmed that the secondary batteries of Examples 1 and 2 have superior capacity characteristics after high-temperature storage, have less volume change, and generate less gas at high temperatures compared to the secondary batteries of Comparative Examples 1 to 5.

Claims

1. A positive electrode active material comprising a lithium transition metal oxide having a form of secondary particles formed by aggregation of primary particles and represented by the following chemical formula 1: The lithium transition metal oxide has a crystal grain size of 160 nm or less and an average primary particle size of 0.6 μm or more; The positive electrode active material has an average secondary particle diameter D 50 The lithium transition metal oxide includes two different types of lithium transition metal oxides, [Chemical formula 1] Li 1+a Ni x Co y Mn z B w O 2 In the above Chemical Formula 1, A positive electrode active material, wherein 0≦a≦0.5, 0.5≦x<1.0, 0<y≦0.4, 0<z≦0.4, and 0<w≦0.

1.

2. 2. The positive electrode active material according to claim 1, wherein boron (B) is contained in an amount of 0.02 to 0.3 parts by weight based on 100 parts by weight of the lithium transition metal oxide.

3. 3. The positive electrode active material according to claim 1, wherein the lithium transition metal oxide has a crystal grain size of 100 nm to 160 nm.

4. The positive electrode active material according to any one of claims 1 to 3, wherein the primary particles of the lithium transition metal oxide have an average particle size of 0.6 µm to 1.3 µm.

5. The positive electrode active material has an average secondary particle diameter D 50 A large particle size lithium transition metal oxide having an average particle size D of 7 μm to 20 μm and a secondary particle having an average particle size D 50 and a small particle size lithium transition metal oxide having a particle size of 1 μm to 7 μm.

6. Providing a transition metal hydroxide precursor; mixing a transition metal hydroxide precursor, a lithium source material and a boron (B)-containing source material, and calcining at 760° C. to 840° C. to produce a boron (B)-doped lithium transition metal oxide; The boron (B)-doped lithium transition metal oxide is represented by the following formula 1, has a crystal grain size of 160 nm or less, and has an average primary particle size of 0.6 μm or more, [Chemical formula 1] Li 1+a Ni x Co y Mn z B w O 2 In the above Chemical Formula 1, A method for producing a positive electrode active material, wherein 0≦a≦0.5, 0.5≦x<1.0, 0<y≦0.4, 0<z≦0.4, and 0<w≦0.

1.

7. The transition metal hydroxide precursor is represented by the following chemical formula 2: [Chemical formula 2] Ni x1 Co y1 Mn z1 (OH) 2 In the above Chemical Formula 2, The method for producing a positive electrode active material according to claim 6 , wherein 0.5≦x1<1.0, 0<y1≦0.4, 0<z1≦0.4, and x1+y1+z1=1.

8. The method for producing a positive electrode active material according to claim 6 or 7, wherein the transition metal hydroxide precursor and the boron (B)-containing raw material are mixed in amounts such that the total moles of transition metals: the moles of boron is 0.97:0.03 to 0.998:0.

002.

9. The method for producing a positive electrode active material according to any one of claims 6 to 8, wherein the lithium source material is mixed in an amount such that a molar ratio of lithium to a total molar number of transition metals and boron is 1.0 to 1.

2.

10. The method for producing a positive electrode active material according to any one of claims 6 to 9, wherein the firing is carried out at 760°C to 800°C for 15 hours to 30 hours.

11. A positive electrode for a lithium secondary battery, comprising the positive electrode active material according to claim 1 .

12. A lithium secondary battery comprising the positive electrode for lithium secondary batteries according to claim 11.

Citation Information

Patent Citations

  • Positive electrode material for lithium-ion secondary battery, and lithium-ion secondary battery using it

    JP2011113825A

  • JPP4131521B

  • Positive electrode active material for secondary battery and secondary battery comprising the same

    KR102004457B1

  • Binder composition for positive electrodes, slurry for positive electrodes, positive electrode and lithium ion secondary battery

    WO2017104178A1

  • Positive electrode active material for nonaqueous electrolyte rechargeable battery, and nonaqueous electrolyte rechargeable battery

    WO2018043189A1